Aqueous dispersion of non-melt-flowable tetrafluoroethylene copolymer
The aqueous dispersion of non-melt-flowable TFE copolymer addresses settling and solidification issues by maintaining a low redispersion sedimentation rate and low perfluorooctanoic acid content, ensuring stable redispersibility and environmental compliance.
Patent Information
- Application Number
- JP2023092383
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-05
- Publication Date
- 2024-12-17
AI Technical Summary
Non-melt-flowable tetrafluoroethylene (TFE) copolymer aqueous dispersions tend to settle over time, leading to solidification and difficulty in redispersing the TFE polymer particles, which results in reduced concentration and waste due to solidification, and environmental concerns from perfluorooctanoic acid and its salts.
Aqueous dispersion of non-melt-flowable TFE copolymer with a redispersion sedimentation rate of 60% or less, a short axis to long axis ratio of 0.7 or more, and perfluorooctanoic acid and its salts content less than 10 ppb, ensuring excellent redispersibility and environmental performance.
The solution provides stable redispersibility of TFE copolymer particles, reducing waste and disposal costs while maintaining high environmental standards by minimizing perfluorooctanoic acid content.
Smart Images

Figure 2024174521000003 
Figure 2024174521000004 
Figure 2024174521000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an aqueous dispersion of a non-melt flowable tetrafluoroethylene copolymer having excellent redispersibility, and more specifically to an aqueous dispersion of a non-melt flowable tetrafluoroethylene (hereinafter referred to as TFE) copolymer, in which the redispersion sedimentation rate of the TFE copolymer is 60% or less, the content of perfluorooctanoic acid and salts thereof is less than 10 ppb, and the ratio of minor axis:major axis of the non-melt flowable TFE copolymer particles is 0.7 or more. [Background technology]
[0002] Polytetrafluoroethylene (PTFE) aqueous dispersions, due to their excellent insulating properties, peelability, good weather resistance, flame retardancy, etc., are used as they are or after concentration in various applications such as electronic materials such as printed circuit boards, raw materials for paints, binders for batteries, additives for various plastics, and PTFE fibers spun into fibers. In addition, paints using PTFE aqueous dispersions are used to coat chemical equipment and glass fabrics, for example, conveyor belts, roofing materials (tent membranes) for membrane-structured buildings, packing, etc.
[0003] The following Patent Document 1 proposes a stable aqueous emulsion containing 1.0% by mass or more of a hydrocarbon-based anionic surfactant relative to a TFE homopolymer (TFE polymer). According to this Patent Document 1, TFE polymer particles are produced in the form of an aqueous emulsion by the emulsion polymerization method disclosed in the following Patent Documents 2 and 3, that is, by forcing TFE into an aqueous medium containing a water-soluble polymerization initiator and an anionic surfactant having a fluoroalkyl group as a hydrophobic group (hereinafter referred to as a fluorine-containing emulsifier) as an emulsifier, and polymerizing the TFE, and an emulsion stabilizer is further added to increase stability.
[0004] Furthermore, the following Patent Document 4 describes a TFE polymer aqueous dispersion having a fluorine-containing emulsifier content of 50 ppm or less, and that the TFE polymer contains at least one monomer selected from the group consisting of fluorinated olefins having 2 to 8 carbon atoms and fluorinated vinyl alkyl ethers having an alkyl portion having 1 to 6 carbon atoms. Also, a method for removing a fluorine-containing emulsifier from a TFE polymer aqueous dispersion by contacting the TFE polymer aqueous dispersion with an anion exchanger is disclosed.
[0005] However, the non-melt-flowable TFE polymer aqueous dispersions used in these methods have the problem that they are prone to settling when left standing for a long period of time, and the TFE polymer that has once settled solidifies and is difficult to redisperse, and further, there is a problem that the TFE polymer concentration in the TFE polymer aqueous dispersion is reduced. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 8-20700 [Patent Document 2] Special table 2010-509441 publication [Patent Document 3] Special Publication No. 2010-509442 [Patent Document 4] Special Publication No. 2002-532583 Summary of the Invention [Problem to be solved by the invention]
[0007] That is, an object of the present invention is to provide an aqueous dispersion of a non-melt flowable TFE copolymer which is excellent in re-dispersibility of non-melt flowable TFE copolymer particles, which are the solid content in the aqueous dispersion of a non-melt flowable TFE copolymer after being left to stand for a long period of time, and which is also excellent in environmental performance. [Means for solving the problem]
[0008] The present invention provides an aqueous dispersion of a non-melt flowable TFE copolymer, in which a redispersion sedimentation rate of a copolymer represented by the following formula (1) is 60% or less, the content of perfluorooctanoic acid and salts thereof in the aqueous dispersion is less than 10 ppb, and the ratio of minor axis:major axis of the non-melt flowable TFE copolymer particles is 0.7 or more.
[0009] Redispersion sedimentation rate (%) = X3 / X2 × 100 (1) During the ceremony, X2: 15 g of an aqueous dispersion of a TFE polymer having the same concentration as the copolymer is centrifuged at 20° C. and 3,000 rpm for 30 minutes in a centrifuge, and then redispersed. The solid sedimentation rate (%) after redispersion is represented by the following formula (2). X3: The solid sedimentation ratio (%) after redispersion, which is represented by the following formula (2), is obtained by centrifuging 15 g of the aqueous dispersion of the copolymer at a temperature of 20° C. and a rotation speed of 3,000 rpm for 30 minutes using a centrifuge and then redispersing the dispersion. Percentage of solids settling after redispersion (%) = (solids settling after redispersion) / (solids mass before centrifugation) × 100 (2)
[0010] In a preferred embodiment of the present invention, the particle size (d50) when the cumulative volume percentage of the copolymer is 50% is 180 nm or less.
[0011] In a preferred embodiment of the present invention, the non-melt-flowable TFE copolymer is a non-melt-flowable copolymer of TFE and at least one comonomer selected from (perfluoroalkyl)ethylene, perfluoro(alkyl vinyl ether), and hexafluoropropylene.
[0012] In a preferred embodiment of the present invention, the perfluoroalkyl group in the (perfluoroalkyl)ethylene is a perfluoroalkyl group having 1 to 10 carbon atoms.
[0013] In a preferred embodiment of the present invention, the (perfluoroalkyl)ethylene is (perfluorobutyl)ethylene.
[0014] In a preferred embodiment of the present invention, the perfluoroalkyl group in the perfluoro(alkyl vinyl ether) is a perfluoroalkyl group having 1 to 10 carbon atoms.
[0015] In a preferred embodiment of the present invention, the perfluoro(alkyl vinyl ether) is at least one selected from perfluoro(ethyl vinyl ether) and perfluoro(propyl vinyl ether).
[0016] In a preferred embodiment of the present invention, the comonomer is contained in an amount of 0.01 to 1.00% by mass based on TFE.
[0017] In a preferred embodiment of the present invention, the comonomer is contained in an amount of 0.01 to 0.50% by mass based on TFE.
[0018] In a preferred embodiment of the present invention, the specific gravity (SSG) of the copolymer is 2.27 or less.
[0019] In a preferred embodiment of the present invention, the amount of perfluorooctanoic acid and salts thereof is less than 1 ppb based on the mass of the aqueous dispersion. Effect of the Invention
[0020] The present invention provides an aqueous dispersion of a non-melt flowable TFE copolymer which is excellent in redispersibility of non-melt flowable TFE copolymer particles, which are the solid content in the aqueous dispersion of a non-melt flowable TFE copolymer, even after being left to stand for a long period of time, and which is also excellent in environmental performance. [Brief description of the drawings]
[0021] [Figure 1] FIG. 2 is a SEM image of the primary particles of Example 2. [Diagram 2]FIG. 2 is a SEM image of the primary particles of Comparative Example 1. [Diagram 3] FIG. 2 is a graph showing the results of a centrifugation sedimentation test and a centrifugation sedimentation redispersion test for Example 1 and Comparative Example 1. [Figure 4] FIG. 2 is a diagram showing the results of a static sedimentation test and a static sedimentation redispersion test for Example 1 and Comparative Example 1. [Diagram 5] Photographs of Example 1 and Comparative Example 1 after standing for 90 days. [Figure 6] Photographs of Example 2 and Comparative Example 1 taken when the containers were inverted after being left to stand for 7 months. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The aqueous dispersion of a non-melt flowable TFE copolymer of the present invention is a non-melt flowable TFE copolymer aqueous dispersion, and important features thereof are that the redispersion sedimentation rate of the copolymer represented by the above formula (1) is 60% or less, the content of perfluorooctanoic acid and its salts in the aqueous dispersion is less than 10 ppb, and the ratio of minor axis:major axis of the non-melt flowable TFE copolymer particles is 0.7 or more. As mentioned above, the TFE polymer particles, which are solids in the aqueous dispersion of non-melt flowable TFE copolymer, tend to settle, so when the aqueous dispersion of TFE polymer is left standing for a long period of time, the TFE polymer particles settle, and the settled TFE polymer particles solidify and are difficult to redisperse by stirring, etc. However, in the aqueous dispersion of non-melt flowable TFE copolymer of the present invention, the redispersion settling rate of the aqueous dispersion of non-melt flowable TFE copolymer is 60% or less, and the ratio of the short diameter:long diameter of the non-melt flowable TFE copolymer particles is 0.7 or more, so that the settled non-melt flowable TFE copolymer particles are prevented from solidifying, and redispersibility can be significantly improved.Furthermore, the content of persistently decomposable perfluorooctanoic acid and its salt is less than 10ppb, so that it is also excellent in environmental performance.
[0023] The fact that the aqueous dispersion of the non-melt-fluid TFE copolymer of the present invention has excellent redispersibility is also evident from the results of the centrifugal sedimentation test, the centrifugal redispersion test, the static sedimentation test, and the static sedimentation redispersion test in the examples described later.
[0024] (Redispersion Sedimentation Rate) As is clear from FIG. 3 showing the results of the centrifugal sedimentation test and the centrifugal sedimentation redispersion test, the aqueous dispersion of the non-melt flowable TFE copolymer of the present invention, in which the redispersion sedimentation rate of the non-melt flowable TFE copolymer aqueous dispersion is 60% or less, has a reduced amount of sedimentation compared to an aqueous dispersion of the TFE polymer in which the redispersion sedimentation rate exceeds 60%. As shown in Examples 1 to 4 described later, it is clear that the aqueous dispersion of the non-melt-flowable TFE copolymer of the present invention can be well redispersed by having a redispersion sedimentation rate represented by the above formula (1) of 60% or less, preferably 50% or less, and more preferably 30% or less. Furthermore, the non-melt-flowable TFE copolymer of the present invention is considered to have excellent sedimentation stability because it contains few rod-shaped particles that are prone to sedimentation.
[0025] When the redispersion sedimentation rate shown by the above formula (1) exceeds 60%, the settled non-melt-fluidity TFE copolymer particles are strongly solidified, making redispersion difficult. In addition, as a result of the settlement of the non-melt-fluidity TFE copolymer particles, which are solid contents, the non-melt-fluidity TFE copolymer particles dispersed in the aqueous dispersion of the non-melt-fluidity TFE copolymer are reduced, which is undesirable. Furthermore, the firmly solidified non-melt-fluidity TFE copolymer must be discarded, which wastes much of the non-melt-fluidity TFE copolymer, which is a useful resource, and also generates disposal costs, which is undesirable from the economic point of view.
[0026] (Non-melt flowable TFE copolymer) The non-melt-flowable TFE copolymer used in the present invention is preferably a non-melt-flowable copolymer of tetrafluoroethylene (TFE) and at least one comonomer selected from perfluoro(alkyl vinyl ether), (perfluoroalkyl)ethylene, and hexafluoropropylene.
[0027] The (perfluoroalkyl)ethylene preferably has a perfluoroalkyl group having 1 to 10 carbon atoms, more preferably at least one selected from (perfluoroethyl)ethylene, (perfluorobutyl)ethylene, (perfluorohexyl)ethylene, and (perfluorooctyl)ethylene, and further preferably (perfluorobutyl)ethylene.
[0028] The perfluoro(alkyl vinyl ether) preferably has a perfluoroalkyl group having 1 to 10 carbon atoms, more preferably at least one selected from perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether) and perfluoro(propyl vinyl ether). Still more preferably, it is perfluoro(ethyl vinyl ether) or perfluoro(propyl vinyl ether).
[0029] The comonomer in the non-melt-flowable TFE copolymer used in the present invention is contained in an amount of 0.01 to 1.00 mass%, preferably 0.01 to 0.50 mass%, more preferably 0.01 to 0.30 mass% based on TFE. When the content of the comonomer is 0.01 to 1.00 mass%, the stability of the aqueous dispersion is improved because there are few rod-shaped particles that tend to settle. On the other hand, when the content of the comonomer exceeds 1.00 mass%, the thermal stability is reduced, which is not preferable. Also, when the content of the comonomer is less than 0.01 mass%, the redispersion sedimentation rate is poor, which is not preferable.
[0030] The melting point of the non-melt flowable TFE copolymer used in the present invention is 320 to 350° C., preferably 334 to 342° C. If the melting point is less than 320° C., the comonomer content in the non-melt flowable TFE copolymer increases, making it difficult to fibrillate, which is not preferred. The non-melt flowable TFE copolymer used in the present invention is a copolymer that does not exhibit melt moldability at temperatures above its melting point, and is preferably a copolymer whose MFR cannot be measured at temperatures above its melting point according to ASTM D1238 (372°C, load 5 kg). Such a non-melt flowable TFE copolymer is different from a TFE copolymer that has melt flowability and is melt moldable.
[0031] The specific gravity (SSG) of the non-melt-flowable TFE copolymer is desirably 2.27 or less, preferably 2.22 or less, and more preferably 2.20 or less. The larger the SSG value, the smaller the molecular weight, and vice versa. Therefore, the smaller the SSG value, i.e., the higher the molecular weight, the better the mechanical properties. On the other hand, the larger the SSG value (over 2.27), i.e., the smaller the molecular weight, the poorer the chemical resistance and heat resistance, which is not preferred.
[0032] The non-melt-flowable TFE copolymer aqueous dispersion of the present invention is an aqueous dispersion in which fine particles (colloidal particles) of a high-molecular-weight non-melt-flowable TFE copolymer are dispersed. The colloidal particles in the non-melt-flowable TFE copolymer aqueous dispersion are desirably colloidal particles having a particle size (d50) at a cumulative volume percentage of 50% of 180 nm or less, preferably 50 to 180 nm, and more preferably 50 to 150 nm. If d50 is smaller than 50 nm, the primary particles may be more likely to aggregate than if it is within the above range, while if d50 exceeds 180 nm, the sedimentation stability (dispersion stability) of the colloidal particles is reduced, which is undesirable.
[0033] The non-melt-flowable TFE copolymer fine particles (colloid particles or primary particles) in the non-melt-flowable TFE copolymer aqueous dispersion of the present invention preferably have a ratio (minor diameter / major diameter) of minor diameter (minimum diameter) to major diameter (maximum diameter) of 0.7 or more. The closer this ratio (minor diameter / major diameter) is to 1, the closer the primary particles are to a perfect circle, which is preferable because it improves the redispersibility of the primary particles, and if it is less than 0.7, it is undesirable because the shape of the primary particles becomes rod-like and the redispersibility is poor.
[0034] In the present invention, the concentration of the non-melt-flowable TFE copolymer in the non-melt-flowable TFE copolymer aqueous dispersion is not particularly limited, but is in the range of 10 to 80 mass%, preferably 15 to 80 mass%, and more preferably 20 to 80 mass%. In order to enhance the dispersion effect of the non-melt fluidity TFE copolymer, the lower the non-melt fluidity TFE copolymer concentration, the more preferable; if the non-melt fluidity TFE copolymer concentration is high, sedimentation stability (dispersion stability) may be impaired, so this is not preferable. On the other hand, when transporting the non-melt fluidity TFE copolymer aqueous dispersion, the higher the concentration, the more the transportation cost can be saved. Therefore, the non-melt fluidity TFE copolymer concentration in the non-melt fluidity TFE copolymer aqueous dispersion of the present invention is preferably 10% by mass or more, particularly in the range of 20 to 80% by mass. The non-melt flowable aqueous TFE copolymer dispersion can also be used by mixing with a non-melt flowable aqueous TFE copolymer dispersion using a different comonomer. Furthermore, in order to enhance the dispersing effect of the non-melt flowable TFE copolymer in the aqueous dispersion of the non-melt flowable TFE copolymer, it is also possible to dilute it with water or various solutions before use.
[0035] In the present invention, the content of perfluorooctanoic acid and its salt in the non-melt flowable TFE copolymer aqueous dispersion is preferably less than 10 ppb, more preferably less than 1 ppb, more preferably 0 ppb, based on the mass of the aqueous dispersion. Since perfluorooctanoic acid and its salt are difficult to decompose and are concerned about their impact on the environment, it is desired that the content be as low as possible. The concentration of perfluorooctanoic acid and its salts in the non-melt flowable TFE copolymer aqueous dispersion can be calculated by freezing 10 ml of the non-melt flowable TFE copolymer aqueous dispersion in a polyethylene container in a -20°C freezer to coagulate the non-melt flowable TFE copolymer and separate it from the water, transferring the entire contents of the polyethylene container to a Soxhlet extractor and extracting with about 80 ml of methanol for 7 hours, and measuring the diluted sample liquid by liquid chromatography.
[0036] There is no particular limitation on the method for preparing a non-melt-flowable aqueous dispersion of a TFE copolymer having a content of perfluorooctanoic acid and its salts of less than 10 ppb. The following method can be exemplified. For example, as disclosed in the above-mentioned Patent Documents 3 and 4, perfluorooctanoic acid and its salts are not used as polymerization agents during polymerization, but ammonium salts of fluoromonoether acids (C3F7-O-CF(CF3)COOH) and fluoropolyether acids (C3F7-O-[CF(CF3)CF2O] n For example, a method for polymerizing a TFE copolymer using an ammonium salt of -CF(CF3)COOH) is used.
[0037] In the present invention, the non-melt flowable TFE copolymer in the aqueous dispersion of the non-melt flowable TFE copolymer is the non-melt flowable TFE copolymer of TFE and the above-mentioned comonomer, and the redispersion sedimentation rate is 60% or less, so that it can obtain excellent redispersion sedimentation rate.In addition, the content of perfluorooctanoic acid and its salt in the aqueous dispersion of the non-melt flowable TFE copolymer is less than 10ppb, so that it also has excellent environmental performance.
[0038] The non-melt-flowable TFE copolymer aqueous dispersion used in the present invention may further contain an emulsion stabilizer in order to enhance the stability of the non-melt-flowable TFE copolymer aqueous dispersion. As the emulsion stabilizer, a hydrocarbon-based anionic surfactant is preferred. This surfactant essentially forms a salt that is insoluble or poorly soluble in water with calcium, aluminum, and iron, which are soil components, and therefore can avoid contamination of rivers, lakes, and groundwater caused by the surfactant.
[0039] Examples of such hydrocarbon-based anionic surfactants include higher fatty acid salts, higher alcohol sulfate salts, liquid fatty oil sulfate salts, fatty alcohol phosphate salts, dibasic fatty acid ester sulfonates, and alkyl aryl sulfonates. In particular, Na, K, Li, and NH4 salts of polyoxyethylene alkyl phenyl ether ethylene sulfonate (polyoxyethylene n is 1 to 6, alkyl has 8 to 11 carbon atoms), alkyl benzene sulfonate (alkyl has 10 to 12 carbon atoms), dialkyl sulfosuccinate (alkyl has 8 to 10 carbon atoms), etc. can be exemplified as preferred ones because they can impart high mechanical stability to a non-melt flowable TFE copolymer aqueous dispersion and prevent aggregation of non-melt flowable TFE copolymer particles due to high speed stirring, etc.
[0040] Furthermore, the aqueous dispersion of the non-melt-flowable TFE copolymer of the present invention does not solidify strongly even after being left to stand for a long period of time, i.e., has excellent redispersibility (low redispersion sedimentation rate), and is therefore preferable from the standpoint of economy, for example, because it enables reduction in disposal costs. EXAMPLES
[0041] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the present invention, the physical properties were measured by the following methods.
[0042] [1] Particle size at cumulative volume percentage 50% (d50) The particle size (d50) of the non-melt-flowable TFE copolymer particles or the particle size (d50) of the TFE polymer particles was measured using a Microtrac UPA150 Model No. 9340 (manufactured by Nikkiso Co., Ltd.).
[0043] [2] Standard specific gravity (SSG) Measured according to ASTM D-4894. A non-melt-flowable TFE copolymer aqueous dispersion or TFE polymer aqueous dispersion obtained by emulsion polymerization was adjusted to a concentration of 15% by mass using pure water. Then, about 750 ml of the non-melt-flowable TFE copolymer aqueous dispersion or TFE polymer aqueous dispersion adjusted to the above concentration was placed in a polyethylene container and vigorously shaken by hand to aggregate and separate the solids. The separated solids were dried at 150°C for 2 hours. 12.0 g of the dried solids (resin powder) were placed in a cylindrical mold with a diameter of 2.85 cm and smoothed, and after 30 seconds, the final pressure was 350 kg / cm. 2 The pressure was gradually increased to 350 kg / cm 2 The preform thus obtained (two pieces per sample) was heated in an air furnace from 290°C to 380°C at 2°C / min, held at 380°C for 30 minutes, cooled to 294°C at 1°C / min, held at 294°C for 1 minute, removed from the furnace, and cooled to room temperature (23±1°C) to prepare a standard sample. The mass ratio of the standard sample to the mass of the same volume of water at room temperature (23±1°C) was used as the standard gravity. In this case, the average of the standard gravity of the two samples was calculated and used as the standard gravity. This standard density serves as a guide for the average molecular weight, and generally the lower the standard density, the higher the molecular weight.
[0044] [3] Comonomer content [3-1] Comonomer content (perfluorobutyl ethylene (PFBE) content) Using the same method as described in [2] above, 0.8±0.050 g of dried solids (resin powder) obtained from a non-melt-flowable TFE·PFBE copolymer aqueous dispersion was placed in a cylindrical mold with a diameter of 2.85 cm and smoothed between aluminum foils. After 30 seconds, the final pressure was 496 kg / cm 2The pressure was gradually increased until the final pressure was reached, and this final pressure was maintained for 2 minutes to obtain a sample for measurement. Similarly, measurement samples were also prepared for resin powders with known PFBE contents (mass%) (two points with PFBE contents of 0 mass% and 0.03 mass%). The infrared spectra of these samples were measured, and the absorbance ratio X was calculated using the following formula (3). Absorbance ratio X=(CB) / (AB)...(3) A:936cm -1 Peak height (absorbance) B:887cm -1 Peak height (absorbance) C:875cm -1 Peak height (absorbance) A calibration curve was created from the PFBE content (mass%) and absorbance ratio X of two samples with known PFBE content (mass%), and the PFBE content (mass%) of the sample was calculated from the absorbance ratio X of the sample.
[0045] [3-2] Comonomer content (perfluoropropyl vinyl ether (PPVE) content) Using the same method as in [2] above, 1.75±0.005 g of dried solids (resin powder) obtained from the non-melt flowable TFE·PPVE copolymer aqueous dispersion was placed in a cylindrical mold with a diameter of 2.85 cm, smoothed between aluminum foil, and pressure was applied for 30 seconds, gradually increasing until the final pressure reached 1470 kg / cm. 2 The final pressure was applied and maintained for 2 minutes to obtain measurement sample 1. Similarly, measurement samples were also prepared for resin powders with known PPVE contents (mass%) (two points with PPVE contents of 0 mass% and 0.75 mass%). The infrared spectra of these samples were measured, and the absorbance ratio and absorbance ratio X1 were calculated using the following equations (4) and (5). Absorbance ratio X1 = (absorbance ratio of sample 1 / absorbance ratio of known resin powder) (4) Absorbance ratio=B1 / A1...(5) A1:936cm -1 Peak height (absorbance) B1:994cm -1 Peak height (absorbance) A calibration curve was created from the PPVE content (mass%) and absorbance ratio X1 of two samples with known PPVE contents (mass%), and the PPVE content (mass%) of the sample was calculated from the absorbance ratio X1 of the sample.
[0046] [3-3] Comonomer content (Hexafluoropropylene (HFP) content) Using the same method as described in [2] above, a 1.75±0.005 g sample of a non-melt flowable TFE-HFP copolymer aqueous dispersion or a dried solid (resin powder) obtained from a TFE polymer aqueous dispersion was placed in a cylindrical mold with a diameter of 2.85 cm, flattened between aluminum foil, and subjected to gradually increasing pressure for 30 seconds until the final pressure reached 1470 kg / cm. 2 The final pressure was applied and maintained for 2 minutes to obtain a sample for measurement. Similarly, measurement samples were prepared for resin powders with known HFP contents (mass%) (three points with HFP contents of 0.06 mass%, 0.08 mass%, and 0.12 mass%). The infrared spectra of these samples were measured, and the absorbance ratio and absorbance ratio X2 were calculated using the following formulas (6) and (7). Absorbance ratio x2 = (absorbance ratio of sample / absorbance ratio of known sample) x 0.42 (6) Absorbance ratio = B2 / A2 (7) A2:936cm -1 Peak height (absorbance) B2:983cm -1 Peak height (absorbance) A calibration curve was created from the HFP content (mass%) and absorbance ratio X2 of three samples with known HFP content (mass%), and the HFP content (mass%) of each sample was calculated from the absorbance ratio X2 of each sample.
[0047] [3-4] Comonomer content (perfluoroethyl vinyl ether (PEVE) content) The infrared spectrum of the dried solids (resin powder) obtained from the non-melt-flowable TFE·PEVE copolymer aqueous dispersion was measured using the same method as in [2] above. However, the infrared spectrum was not measurable because it was an extrapolation of the calibration curve using PEVE powder with a known infrared spectrum. Therefore, according to the following formula, it was assumed that all of the PEVE (4.4 g) added was consumed in the polymerization. The maximum comonomer content (%) was calculated by dividing the amount of PEVE added by the mass of the solids (1,189.4 g), which was less than 1 mass%. PEVE content (mass%) (maximum value) = PEVE input amount (4.4g) / solid content (1189.4g) x 100
[0048] [4] Solid content mass% Less than 6 g of non-melt-flowable TFE copolymer aqueous dispersion or TFE polymer aqueous dispersion was weighed into a tared aluminum dish, and the mass (mass before drying) of the non-melt-flowable TFE copolymer aqueous dispersion or TFE polymer aqueous dispersion was measured (measured to four decimal places).Then, the mixture was left to stand in a 105°C dryer for 2 hours to remove moisture, baked in a constant temperature oven at 380°C for 20 minutes, cooled to room temperature, and then the mass (mass after drying) was measured, and the solid content (mass %) was calculated using the following formula (8). Solid content mass% = [(mass after drying - tare mass of aluminum dish) / mass before drying] x 100 (8)
[0049] [5] Melting point In the same manner as in [2] above, 10.0±0.3 mg of a non-melt-flowable TFE copolymer aqueous dispersion or a dried solid (resin powder) obtained from a TFE polymer aqueous dispersion was placed in a measurement Super Clean aluminum sample pan (manufactured by PerkinElmer Japan Co., Ltd.), and then a cover was placed on it and the sample was sealed using a standard crimper press to prepare a measurement sample. The measurement sample was subjected to a power compensation type differential scanning calorimeter Diamond DSC (manufactured by PerkinElmer Japan Co., Ltd.) using an empty Super Clean aluminum sample pan as the reference material, while heating from 200°C to 370°C at a rate of 10°C per minute, and the calorific value was measured. The temperature at the point where the endothermic peak was maximum as a result of the measurement was determined as the melting point of the measurement sample (resin powder).
[0050] [6] Centrifugal sedimentation test 15 g of non-melt fluid TFE copolymer aqueous dispersion or TFE polymer aqueous dispersion having the composition shown in Table 1 was placed in a centrifuge tube (Corning, 15 ml centrifuge tube), and centrifuged for 30 minutes at 20° C. and 3000 rpm using a centrifuge (Kubota, Tabletop Cooled Centrifuge 5500, Angle Rotor RA508). After centrifugation, the solids other than the solids that had settled to the bottom of the centrifuge tube (liquid part: supernatant and solids that had not settled) were removed from the centrifuge tube, the centrifuge tube was left in an upside-down state for 30 minutes, the liquid part was further removed, and the mass (the sum of the mass of the centrifuge tube and the mass of the solids that had settled to the bottom of the centrifuge tube) was measured, and the mass obtained by subtracting the mass of the centrifuge tube from the mass was used as the amount of solids that had settled, and the solids settling ratio was calculated from the following formula (10) and the settling rate was calculated from the following formula (9).
[0051] Sedimentation rate (%) = X1 / X0 × 100 (9) During the ceremony, X0: solid sedimentation ratio (%) represented by the following formula (10) when 15 g of the TFE polymer aqueous dispersion shown in Comparative Example 1 is centrifuged by a centrifuge at a temperature of 20° C. and a rotation speed of 3,000 rpm for 30 minutes, and then the solid content other than the solid content that has settled to the bottom of the centrifuge tube (liquid portion: supernatant and unsettled solid content) is removed. X1: The solid sedimentation ratio (%) shown by the following formula (10) when 15 g of a non-melt-flowable TFE copolymer aqueous dispersion shown in the Examples is centrifuged at a temperature of 20° C. and a rotation speed of 3,000 rpm for 30 minutes in a centrifuge, and then the solid content other than the solid content that has settled to the bottom of the centrifuge tube (liquid portion: supernatant and non-settled solid content) is removed. Percentage of settled solids (%) = (amount of settled solids) / (mass of solids before centrifugation) ×100···(10)
[0052] [7] Centrifugal redispersion test The mass of the centrifuge tube from which the liquid portion was removed in [6] above was measured, 10 g of pure water was added to the centrifuge tube, and the solids that had settled to the bottom of the centrifuge tube were ultrasonically dispersed at 38 kHz for 1 minute. After that, all the solids other than those that had settled to the bottom of the centrifuge tube (the liquid portion and the redispersed solids) were removed, and the centrifuge tube was left in an inverted position for 30 minutes to further remove the liquid portion. The weight (the sum of the mass of the centrifuge tube and the mass of the solids that had settled to the bottom of the centrifuge tube) was measured, and the mass obtained by subtracting the mass of the centrifuge tube from this was determined as the amount of solids that had settled after redispersion. The solids settling ratio after redispersion was calculated from the following formula (2'), and the redispersion settling rate was calculated from the following formula (1').
[0053] Redispersion sedimentation rate (%) = X3 / X2 × 100 (1') During the ceremony, X2: The solid sedimentation ratio (%) represented by the following formula (2') when 15 g of the aqueous dispersion of the TFE polymer shown in Comparative Example 1 was centrifuged at a temperature of 20°C and a rotation speed of 3,000 rpm for 30 minutes using a centrifuge and then redispersed. X3: The solid sedimentation ratio (%) shown by the following formula (2') when 15 g of a non-melt-flowable TFE copolymer aqueous dispersion shown in the Examples was centrifuged at a temperature of 20°C and a rotation speed of 3,000 rpm for 30 minutes in a centrifuge and then redispersed. Percentage of solids settling after redispersion (%) = (amount of solids settling after redispersion) / (Solid mass before centrifugation) × 100 (2')
[0054] [8] Static settling test As shown in Table 2, 15 g of non-melt fluid TFE copolymer aqueous dispersion or TFE polymer aqueous dispersion was placed in a centrifuge tube, and after closing the mouth of the centrifuge tube, it was left standing at room temperature for 30 days, 60 days, and 90 days, respectively. After leaving it standing for 30 days, 60 days, and 90 days, the mouth of the centrifuge tube was opened, and the solids other than the settled solids (liquid part: supernatant and solids that did not settle) were removed, and the centrifuge tube was left standing for 30 minutes in an upside-down state to further remove the liquid part, and its mass (the sum of the mass of the centrifuge tube and the mass of the solids that settled at the bottom of the centrifuge tube) was measured, and the mass obtained by subtracting the mass of the centrifuge tube from the mass was regarded as the amount of settled solids after standing, and the solids settling ratio was calculated from the following formula (12) and the settling rate was calculated from the following formula (11).
[0055] Sedimentation rate (%)=X5 / X4× 100...(11) During the ceremony, X4: the solid sedimentation ratio (%) represented by the following formula (12) when 15 g of the TFE polymer aqueous dispersion shown in Comparative Example 1 was left to stand at room temperature for 30 days, 60 days, and 90 days after closing the mouth of the centrifuge tube, and then other than the settled solids (liquid part: supernatant and non-settled solids) was removed, the centrifuge tube was left to stand for 30 minutes in an upside-down position, and the liquid part was further removed. X5: 15 g of a non-melt-flowable TFE copolymer aqueous dispersion shown in the Examples was left to stand at room temperature for 30 days, 60 days, and 90 days after closing the mouth of a centrifuge tube, and then everything other than the settled solids (liquid part: supernatant and non-settled solids) was removed, and the centrifuge tube was left to stand for 30 minutes in an upside-down position to further remove the liquid part. The amount of settled solids after standing was measured, and this is the solids settling ratio (%) shown by the following formula (12). Solids settling ratio (%) = (Solids settling amount after standing) / (Solids mass before standing) ×100 ···(12)
[0056] [9] Static settling and redispersion test The mass of the test tube that was left standing in [8] above was measured, 10 g of pure water was added to the centrifuge tube, and the solids that had settled to the bottom of the centrifuge tube were ultrasonically dispersed at 38 kHz for 1 minute. After that, all the solids other than those that had settled to the bottom of the centrifuge tube (the liquid portion and the redispersed solids) were removed, and the centrifuge tube was left standing upside down for 30 minutes to further remove the liquid portion. The mass (the sum of the mass of the centrifuge tube and the amount of solids that had settled to the bottom of the centrifuge tube) was measured, and the mass obtained by subtracting the mass of the centrifuge tube from this was regarded as the amount of solids that had settled after redispersion. The redispersed solids settling ratio was calculated from the following formula (14), and the redispersion settling rate was calculated from the following formula (13).
[0057] Redispersion sedimentation rate (%) = X7 / X6 × 100 (13) During the ceremony, X6: the solid sedimentation ratio (%) represented by the following formula (14) when 15 g of the TFE polymer aqueous dispersion shown in Comparative Example 1 was left to stand at room temperature for 30 days, 60 days, and 90 days after closing the mouth of the centrifuge tube, and then other than the settled solids (liquid part: supernatant and non-settled solids) was removed, the centrifuge tube was left to stand in an upside-down position for 30 minutes, the liquid part was further removed, and the dispersion was redispersed. X7: the solid sedimentation ratio (%) represented by the following formula (14) when 15 g of a non-melt-flowable TFE copolymer aqueous dispersion shown in the Examples is allowed to stand at room temperature for 30 days, 60 days, or 90 days after closing the mouth of a centrifuge tube, and then the solids other than the settled solids (liquid portion: supernatant and non-settled solids) are removed, the centrifuge tube is allowed to stand upside down for 30 minutes, the liquid portion is further removed, and the dispersion is redispersed. Percentage of solids settling after redispersion (%) = (amount of solids settling after redispersion) / (Solid mass before centrifugation) × 100 (14)
[0058]
[10] Ratio of minor axis to major axis of primary particles For the primary particles of non-melt-flowable TFE copolymer obtained by polymerization, 10 particles were randomly selected from the SEM images obtained at a magnification of ×20K using a scanning electron microscope (SEM), and the maximum diameter (A) and minimum diameter (B) of the particles were measured in mm units, and the ratio of minimum diameter (B) / maximum diameter (A) was calculated. The average value of the ratios of minimum diameter (B) / maximum diameter (A) for the 10 points was taken as the ratio of minimum diameter (B) / maximum diameter (A) of the target primary particle. The closer this ratio of minimum diameter (B) / maximum diameter (A) is to 1, the closer the primary particle is to a perfect circle. Note that bent rod-shaped or string-shaped particles were excluded from the random selection because they could not be calculated as circular or elliptical.
[0059] Example 1 (Polymerization of non-melt-flowable TFE copolymers) In a 4-liter stainless steel (SUS316) autoclave equipped with a stirring blade and a temperature-control jacket, 60 g of paraffin wax, 2087 ml of deionized water, 12.03 g of the ammonium salt of fluoromonoether acid (formula C3F7-O-CF(CF3)COOH), 12.03 g of fluoropolyether acid (C3F7-O-[CF(CF3)CF2O] n 1.0g of ammonium salt of -CF(CF3)COOH) and 0.01g of polyoxyethylene alkylphenyl ether were charged, and the system was replaced with nitrogen gas three times while heating to 80℃ to remove oxygen, and then vacuum was drawn. After that, 4.4g of PFBE, 0.2g of ammonium salt of fluoromonoether acid, and 199.8ml of deionized water were charged, and tetrafluoroethylene (TFE) was supplied to set the internal pressure to 1.90-1.98MPa, and the internal temperature was maintained at 80℃ while stirring at 110 rpm.
[0060] Next, 100 ml of the aqueous solution was pumped from an aqueous solution of 0.12 g of ammonium persulfate dissolved in 400 ml of water. After the injection of the aqueous ammonium persulfate solution was completed, TFE was continued to be supplied so as to maintain the internal pressure at 2.0 MPa. When the consumption of TFE reached 1106.79 g, stirring was stopped. The gas in the autoclave was released to normal pressure, a vacuum was drawn, and the pressure was returned to normal pressure with nitrogen gas, after which the contents were removed and the reaction was terminated, and a non-melt flowable TFE copolymer aqueous dispersion was obtained.
[0061] The non-melt flowable TFE copolymer aqueous dispersion obtained was measured for particle size (d50) at cumulative volume percentage 50%, minor axis / major axis ratio of primary particles, SSG, PFBE content, solid mass, melting point, and amount of perfluorooctanoic acid and its salts. In addition, a centrifugal sedimentation test and a centrifugal sedimentation redispersion test were performed. The results are shown in Table 1 and Figure 3.
[0062] (Examples 2 to 4) (Polymerization of non-melt-flowable TFE copolymers) In a 4-liter stainless steel (SUS316) autoclave equipped with a stirring blade and a temperature-control jacket, 60 g of paraffin wax, 2087 ml of deionized water, 12.03 g of the ammonium salt of fluoromonoether acid (formula C3F7-O-CF(CF3)COOH), 12.03 g of fluoropolyether acid (C3F7-O-[CF(CF3)CF2O] n 1.0 g of ammonium salt of -CF(CF3)COOH) and 0.01 g of polyoxyethylene alkylphenyl ether were charged, and the system was purged with nitrogen gas three times while heating to 80°C to remove oxygen, and then vacuum was drawn. Then, a comonomer (HFP, PPVE, or PEVE) was pumped in the amount shown in Table 1 using a pump. Then, tetrafluoroethylene (TFE) was fed to set the internal pressure to 1.90-1.98 MPa, and the internal temperature was maintained at 80°C while stirring at 110 rpm.
[0063] Next, 100 ml of the aqueous solution was pumped from an aqueous solution of 0.12 g of ammonium persulfate dissolved in 400 ml of water. After the injection of the aqueous ammonium persulfate solution was completed, TFE was continued to be supplied so as to maintain the internal pressure at 2.0 MPa. When the consumption of TFE reached 1106.79 g, stirring was stopped. The gas in the autoclave was released to normal pressure, a vacuum was drawn, and the pressure was returned to normal pressure with nitrogen gas, after which the contents were removed and the reaction was terminated, and a non-melt flowable TFE copolymer aqueous dispersion was obtained.
[0064] The non-melt flowable TFE copolymer aqueous dispersion obtained was measured for particle size (d50) at a cumulative volume percentage of 50%, the ratio of the minor axis to the major axis of the particle, SSG, PFBE content, solid mass, melting point, and the amount of perfluorooctanoic acid and its salts. In addition, a centrifugal sedimentation test and a centrifugal sedimentation redispersion test were performed. The results are shown in Table 1. Also, an SEM image of the primary particles of Example 2 is shown in Figure 1.
[0065] Comparative Example 1 For a TFE polymer aqueous dispersion (Teflon (registered trademark) PTFE Dispersion 312-JR, manufactured by Mitsui-Chemours Fluoroproducts Co., Ltd.), the particle size (d50) at a cumulative volume percentage of 50%, the minor axis / major axis ratio of the primary particles, SSG, solid content mass, and the amount of perfluorooctanoic acid and its salts were measured. In addition, a centrifugal sedimentation test and a centrifugal sedimentation redispersion test were conducted. Furthermore, physical property analysis was performed in the same manner as in Example 1. The results are shown in Table 1. Also, an SEM image of the primary particles of Comparative Example 1 is shown in Figure 2.
[0066] Furthermore, a static sedimentation test and a static sedimentation redispersion test were carried out for Example 1 and Comparative Example 1. The results are shown in Table 2 and Figure 4. Furthermore, Figure 5 shows photographs of Example 1 and Comparative Example 1 after standing for 90 days.
[0067] 6 shows photographs of the containers inverted after standing for 7 months for Example 2 and Comparative Example 1. No precipitate was observed in Example 2, but a precipitate of the TFE polymer (white precipitate) was observed in Comparative Example 1.
[0068] [Table 1]
[0069] [Table 2] [Industrial Applicability]
[0070] The aqueous dispersion of the non-melt-flowable TFE copolymer of the present invention has excellent surface properties, heat resistance, chemical resistance, electrical properties, and the like, and therefore, taking advantage of these properties, it can be suitably used as a coating agent for metals, etc., an impregnating agent for fibers and woven fabrics, etc., and as a compounding agent for various plastics, such as an additive for imparting flame retardancy to thermoplastic resins such as polycarbonate.
Claims
1. An aqueous dispersion of a non-melt-flowable tetrafluoroethylene copolymer, characterized in that the redispersion sedimentation rate of a copolymer represented by the following formula is 60% or less, the content of perfluorooctanoic acid and its salts in the aqueous dispersion is less than 10 ppb, and the ratio of minor axis:major axis of the non-melt-flowable tetrafluoroethylene copolymer particles is 0.7 or more. Redispersion sedimentation rate (%) = X 3 / X 2 × 100 During the ceremony, X 2 The percentage of solids sedimented after redispersion (%) is calculated based on the following formula: 15 g of an aqueous dispersion of a tetrafluoroethylene polymer having the same concentration as the copolymer is centrifuged at 20° C. and 3,000 rpm for 30 minutes in a centrifuge and then redispersed. X 3 The percentage of solids sedimented after redispersion (%) is calculated based on the following formula when 15 g of the aqueous dispersion of the copolymer is centrifuged at 20° C. and 3,000 rpm for 30 minutes and then redispersed. Percentage of solids settling after redispersion (%) = (amount of solids settling after redispersion) / (mass of solids before centrifugation) x 100
2. 2. The non-melt-flowable aqueous dispersion of tetrafluoroethylene copolymer according to claim 1, wherein the particle size (d50) at a cumulative volume percentage of 50% of the copolymer is 180 nm or less.
3. The aqueous dispersion of a non-melt-flowable tetrafluoroethylene copolymer according to claim 1 or 2, wherein the non-melt-flowable tetrafluoroethylene copolymer is a non-melt-flowable copolymer of tetrafluoroethylene and at least one comonomer selected from the group consisting of (perfluoroalkyl)ethylene, perfluoro(alkyl vinyl ether), and hexafluoropropylene.
4. 4. The aqueous dispersion of a non-melt-flowable tetrafluoroethylene copolymer according to claim 3, wherein the non-melt-flowable tetrafluoroethylene copolymer is a non-melt-flowable copolymer of tetrafluoroethylene and hexafluoropropylene.
5. 4. The non-melt-flowable aqueous dispersion of a tetrafluoroethylene copolymer according to claim 3, wherein the perfluoroalkyl group in the (perfluoroalkyl)ethylene is a perfluoroalkyl group having 1 to 10 carbon atoms.
6. 6. The non-melt-flowable aqueous dispersion of tetrafluoroethylene copolymer according to claim 5, wherein said (perfluoroalkyl)ethylene is (perfluorobutyl)ethylene.
7. 4. The non-melt-flowable aqueous dispersion of a tetrafluoroethylene copolymer according to claim 3, wherein the perfluoroalkyl group in said perfluoro(alkyl vinyl ether) is a perfluoroalkyl group having 1 to 10 carbon atoms.
8. 8. The non-melt-flowable aqueous dispersion of tetrafluoroethylene copolymer according to claim 7, wherein the perfluoro(alkyl vinyl ether) is at least one selected from perfluoro(ethyl vinyl ether) and perfluoro(propyl vinyl ether).
9. 4. The non-melt-flowable aqueous dispersion of a tetrafluoroethylene copolymer according to claim 3, wherein the comonomer is contained in an amount of 0.01 to 1.00% by mass based on the tetrafluoroethylene.
10. 4. The non-melt-flowable aqueous dispersion of a tetrafluoroethylene copolymer according to claim 3, wherein the comonomer is contained in an amount of 0.01 to 0.50% by mass based on the tetrafluoroethylene.
11. 3. The non-melt-flowable aqueous dispersion of a tetrafluoroethylene copolymer according to claim 1, wherein the specific gravity (SSG) of the copolymer is 2.27 or less.
12. 3. The non-melt-flowable aqueous dispersion of a tetrafluoroethylene copolymer according to claim 1, wherein the content of said perfluorooctanoic acid and its salts in said aqueous dispersion is less than 1 ppb.
Citation Information
Patent Citations
JP1975009441A
Fluoropolymer aqueous emulsion and its production
JP1996020700A
Aqueous dispersion of fluoropolymer
JP2002532583A
Aqueous polymerization of fluorinated monomers using polymerization agents containing fluoropolyetheric acid or salt and short-chain fluorinated surfactants
JP2010509442A
